What do the relationships between functional classification systems of children with cerebral palsy tell us? - Mutlu, Akmer; Pistav-Akmese, Pelin; Yardımcı, Bilge Nur; Ogretmen, Tuncay (Journal of physical therapy science, 2016)
[Purpose] To examine the distribution of and relationship between the Gross Motor Function, Manual Ability, and Communication Function Classification Systems in different limbs of children with spastic cerebral palsy. We also investigated whether the four predicting variables of gender, age, manual ability, and gross motor classifications could significantly predict effective and non-effective communicator groups in communication function. [Subjects and Methods] This retrospective cross-sectional study included 327 children with a mean age of 10.13 ± 4.09 years. Classifications were performed by an experienced pediatric physiotherapist. [Results] Gross motor function levels showed a strong correlation with manual ability levels (r =0.78). Manual ability level was strongly correlated with communication function levels (r =0.73), particularly in quadriplegic children (r =0.78). Gross motor function levels were moderately correlated with communication function levels (r =0.71). Effective communicators in communication function showed more functional levels of manual ability and were determined by Gross Motor Function classifications. The variables were better at predicting ineffective communicators (91% correct) compared with effective communicators (85% correct). [Conclusion] Further studies are needed to relate these functional performance systems to the activity and participation levels as well as the quality of life, desires, and participation of the subjects.